Adrenaline aggravates lung injury caused by liver ischemia–reperfusion and high-tidal-volume ventilation in rats. Issue 1 (December 2016) - Ota, Shuhei; Yazawa, Takuya; Tojo, Kentaro; Baba, Yasuko; Uchiyama, Munehito; Goto, Takahisa; Kurahashi, Kiyoyasu
Abstract Background We often administer adrenaline to improve hypotension of patients undergoing systemic inflammation that is not treated with volume resuscitation. The effects of adrenaline on injured lungs during shock status have not been elucidated. We previously demonstrated that hepatic ischemia–reperfusion followed by high-tidal-volume ventilation-induced systemic inflammation, hypotension, and lung injury in rats. Using this animal model, we investigated the effects of adrenaline on lung injury and hemodynamics. Methods Anesthetized rats were ventilated and underwent hepatic inflow interruption for 15 min twice. After the second liver ischemia–reperfusion, the tidal volume was increased to 24 ml · kg−1 body weight from 6 ml · kg−1, and 12 rats in each group were observed for 360 min after reperfusion with or without continuous intravenous adrenaline administration. Extra fluid was administered according to the decline in the arterial blood pressure. Results Adrenaline administration significantly reduced the volume of intravenous resuscitation fluid. The wet-to-dry weight ratio of the lungs was higher (7.53 ± 0.37 vs. 4.63 ± 0.35, P  < 0.001), the partial oxygen pressure in arterial blood was lower (213 ± 48 vs. 411 ± 33, P  = 0.004), and the tumor necrosis factor-α concentration in bronchoalveolar lavage (BAL) fluid was higher (102.64  ± 100.22 vs. 101.91  ± 100.27, P  = 0.015), with adrenaline. Histopathological examinations revealed marked exudation in the alveolar spaces in rats receiving adrenaline. Conclusions Continuous administration of adrenaline partially prevented a rapid decline in blood pressure but deteriorated lung injury in a rat model of liver ischemia–reperfusion with high-tidal-volume ventilation. A possibility that adrenaline administration aggravate ventilator-induced lung injury during systemic inflammation should be considered.